Rich environments for active learning in action: problem-based learning - Scott Grabinger; Joanna C. Dunlap; Judith A. Duffield (Association for Learning Technology, 1997)
In today's complex world of rapid change, of increasing innovation and of proliferating knowledge, employers and employees must be able to apply tools and knowledge to new situations with increasing frequency to remain productive and competitive (see Nash, 1994). Because we face an environment in which knowledge and skills become rapidly obsolete, people need to know how to be involved in a continual process of 'retooling' their knowledge and skill base (see Swanson et al, 1993). Consequently, learning to think critically, to analyse and synthesize information to solve technical, social, economic, political, and scientific problems, and to engage in lifelong learning, are crucial for successful and fulfilling participation in our competitive society. Learning environments which prepare learners for the complexities of the professional world utilize instructional activities reflecting the problemsolving and challenge-meeting process professionals use on their jobs. Learners need to: • determine for themselves what issues need to be addressed when facing a new problem; • identify knowledge and skills they already possess that can be applied to the situation; • determine which skill and knowledge areas are deficient, arid create learning plans to address those deficiencies; • create timelines, manage resources, and monitor their progress; • apply what they know to problems that may change substantially from one moment to another; and • assess their performance and make changes in personal processes for use to meet subsequent challenges.